Deep Learning Driven Drug Discovery: Tackling Severe Acute Respiratory Syndrome Coronavirus 2 - Zhang, Yang; Ye, Taoyu; Xi, Hui; Juhas, Mario; Li, Junyi (Frontiers in Microbiology, 2021)
Deep learning significantly accelerates the drug discovery process, thus contributing greatly to global efforts to stop the spread of infectious diseases. Besides enhancing the efficiency of screening of antimicrobial compounds against a broad spectrum of pathogens, deep learning has also the potential to efficiently and reliably identify drug candidates against Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). In this mini-review, the recent advances and future perspectives of deep learning-based drug discovery for SARS-CoV-2 are discussed.